Contact time analysis for adsorption process in dechlorination - Amatya, Iswar Man (Nepalese Journal of Engineering, 2005)
Contact time analysis in dechlorination for adsorption process is the subject of the investigation. The contact time in water was performed in batch reactor. Equilibrium studies were conducted over PC, PAC, PACC, GC, GAC, and GACC by using known chlorine solution of concentration 1 and 10 mg/l as adsorbate. The equilibrium studies were performed in several 250ml. bottles. The bottles with adsorbent and adsorbate were placed in shaker at 50- 60 rpm. and samples were withdrawn from 15min to 24hr shaking periods. The residual concentrations in solution were tested by DPD titrimetric standard method. The equilibrium time of 90 % adsorption of the adsorbed amount was calculated as contact time. The result demonstrated that the contact time increases and the rate of adsorption, k decreases with an increment of adsorbent size. Adsorption rate constant was found significantly dependent with particle size of 0.150 to 1.0 mm, where sharp decrease of reaction rate was observed with increase in particle size. Activation of locally available charcoal was found insignificant in dechlorination for adsorption process. Keywords: Adsorption rate constant, Ammonia, Charcoal, Chlorination, Groundwater Nepalese Journal of Engineering Vol.1(1) 2005 pp.46-50